RELATIONSHIP BETWEEN IMPLEMENTATION OF NURSING ROUNDS AND PATIENT SATISFACTION IN INPATIENT ROOMS - Setiawan , Cencen Hendra; Mediawati , Ati Surya; Yudianto , Kurniawan (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective : The purpose of the study was to determine the relationship between the implementation of nursing rounds and patient satisfaction in the Darussalam 5 room of Al Islam Hospital Bandung. Methods : This type of research is correlational with a cross sectional approach. The number of samples in this study were 30 respondents. Sampling technique with quota sampling method. The patient satisfaction instrument uses the patient satisfaction with nursing care quality questionnaire (PSNCQQ) while the nursing rounds instrument uses standardized instruments at Al Islam Hospital Bandung . The analysis used was univariate and bivariate analysis using the fisher exact test. Results : Showed that there was a relationship between the implementation of nursing rounds and patient satisfaction (p=0.002), this indicates that there is a relationship between the implementation of nursing rounds and patient satisfaction in the Darussalam 5 room of Al Islam Hospital Bandung Conclusion : The implementation of nursing rounds by nurses is related to patient satisfaction.